Paradigma Pemahaman Hadis: (Studi Pemahaman Hadis Berdasarkan Bentuk Matan) - Ermawati Usman (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2021)
The scholars look for formulas and strategies to explain the meaning of hadith. Many methods, techniques and approaches are offered by hadith scientists to pave the way for understanding hadith so that hadith which is a product of the past can be kept up to date and become a guide for Muslims who are rahmatan lil alamin. To obtain a comprehensive understanding of the matan of hadith, one way is to have knowledge of the form of matan used by the Prophet Muhammad in the expression of hadith. The forms of hadith expressions referred to are Jawamil kalim, tamsil, ramzi, qiyas and conversational forms, which are the privileges of the Prophet Muhammad in conveying hadith. The five features are adapted to the case faced by the Prophet Muhammad, and cannot be focused on a particular hadith. Thus, the language of the Prophet's da'wah has a meaning value package in conveying parables and symbolic expressions for friends' questions. The expression in the form of matan, can be one of the tools in understanding hadith. This paper will describe the traditions that have the forms of matan which contain the five styles of language above, by presenting several examples that are elaborated on the thoughts or understandings of the hadith scholars.